PERIPROSTATIC NERVE BLOCK AND INTRAPROSTATIC INFILTRATION ON TRUS-P GUIDED BIOPSY - Rachman, Wendi; Safriadi, Ferry (Indonesian Journal of Urology, 2013)
Objective: This study is aimed to determine the effectiveness and complications of periprostatic block and intraprostatic infiltration anesthesia for transrectal prostate biopsy. Material & Method: Two consecutive group of patients, periprostatic block (group A) and intraprostatic infiltration (group B), underwent transrectal ultrasound (TRUS) guided prostate biopsy were entered into the study. Exclusion criteria were severe systemic infection, local infection (prostatitis, proctitis, anorectal abscess, and fissure), hemorrhoid (external and/or internal), and chronic pelvic pain (bladder pain syndrome (BPS) or other pelvic disease. Each group enrolled 58 patients. The patients were requested to choose indicate degree of pain on visual analog score (VAS) 3 times, during probe insertion (VAS1), during anesthesia (VAS2), and during the biopsy (VAS3). Complications from the procedures were recorded. The data were analyzed using Mann-Whitney and independent t-test. Results: There were no significant difference in average age of groups, 65,69 ± 7,019 years for group A and 65,34 ± 7,633 years for group B (p = 0,647). The VAS3 score of group B 5,17 ± 0,653 was significantly lower than group A 5,9 ± 0,612 (p < 0,001). The change in VAS score (VAS3-VAS2) in group B 0,55 ± 0,535 also significantly lower than group A 1,00 ± 0,530 (p = 0,004). The average days with pain were not significant on both group, group A 1,16 ± 0,362 day and group B 1,12 ± 0,329 day (p = 0,594). The duration of bleeding was significantly higher on group B 1,32 ± 0,562 day than group A 1,10 ± 0,307 day (p = 0,026). Conclusion: Intraprostatic infiltration resulted in less pain during prostate biopsy, but also reported more bleeding after the procedure than the periprostatic block.Keywords: Intraprostatic infiltration, periprostatic nerve block, transrectal ultrasound guided prostate biopsy.